Pemberdayaan Kader dalam Upaya Peningkatan Pengetahuan dan Sikap Remaja Putri tentang Anemia - Yusni Podungge; Sri Nurlaily Z; Sri Yulianti Mile (Universitas Muhammadiyah Semarang, 2022)
According to WHO, 2015 anemia is caused by iron deficiency, where one of the high-risk groups is adolescents. In developing countries, adolescent girls who experience anemia at an average age of 10-18 years reach 41.5%. Likewise in Indonesia, young women who experience iron deficiency anemia are as much as 51.7%. The implementation of youth Posyandu activities in Bone Bolango Regency aims to make it easier for the community, especially teenagers, to get health services in an effort to increase awareness and preparedness for risks that can cause adolescent health problems. Based on a preliminary study at the Posyandu at the Botupingge Health Center, Bone Bolango Regency, it was found that the total number of adolescents was 220 people, and only 12 people detected anemia. This situation shows that the coverage of youth posyandu visits is still low so that anemia is not detected in adolescents. The screening for early detection of anemia by health workers and the community is more focused on pregnant women. The provision of health education about anemia in adolescents has been carried out at the Youth Posyandu, but in its implementation and implementation it is not running effectively. Therefore, it is very necessary to refresh Posyandu cadres, especially regarding anemia. The targets of community service are Posyandu cadres and young women. This activity was carried out in the form of material refresher for youth cadres through lectures, discussions, demonstrations, practice of identifying signs and symptoms of anemia, cadre assistance through WhatsApp groups, Youth Posyandu services and knowledge evaluation through questionnaires and observation sheets.